Enhancing Leaf Potassium and Corn Yield in Degraded Ultisols with Vermicompost Fertilizer - Sanjaya, Rina; Riwandi; Hasanudin (TERRA : Journal of Land Restoration, 2023)
The study addresses the constraints of Ultisols and underscores the need for vermicompost fertilizer application. The primary objective is to assess whether augmenting the quantity of vermicompost fertilizer enhances potassium (K) levels in leaves and subsequently boosts corn yields. The research spanned from June to December 2022 in Sri Kuncoro Village, Pondok Kelapa District, Central Bengkulu Regency. Employing a Randomized Complete Block Design (RCBD) with 5 treatment levels and 5 replications resulted in 25 plots, encompassing doses of 0, 7.5, 13, 22.5, and 30 tons per hectare. Upon analyzing the data, it is evident that applying vermicompost fertilizer at a rate of 30 tons per hectare leads to a 1.4093% increase in leaf K levels, a K uptake of 3.2035 g tons-1, and a dry stover weight of 232.351 g tons-1. However, there is no  significant evidence indicating an increase in root dry weight, shoot dry weight, cob weight without husk, and dry shell weight